2020
DOI: 10.1016/j.envint.2020.105800
|View full text |Cite
|
Sign up to set email alerts
|

Estimating traffic contribution to particulate matter concentration in urban areas using a multilevel Bayesian meta-regression approach

Abstract: Highlights A systematic review was conducted on traffic contribution estimates reported by 155 previous studies. Our analysis included 169 cities worldwide. Traffic contribution to PM in Europe, North America and Oceania is 36% lower than other regions. Traffic contribution is 28% lower among studies published after 2005. Traffic contribution is 24% lower among cities with less than 500,000 inhabitants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The effects of road traffic on air quality in large cities have been studied for years and the main pollutants emitted by vehicles are: particulate matter with a diameter lower than 10 μm (PM 10 ) ( Heydari et al, 2020 ; Ionescu et al, 2013 ; Pant and Harrison, 2013 ; Thorpe and Harrison, 2008 ), black carbon ( Ali et al, 2020 ; Invernizzi et al, 2011 ), CO 2 ( Zheng et al, 2020 ) and nitrogen dioxide (NO 2 ) ( Agudelo-Castañeda et al, 2020 ; Degrauewe et al, 2019 ). In the literature there are many works on the quantification and modelling of the dispersion of pollutants from their sources.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of road traffic on air quality in large cities have been studied for years and the main pollutants emitted by vehicles are: particulate matter with a diameter lower than 10 μm (PM 10 ) ( Heydari et al, 2020 ; Ionescu et al, 2013 ; Pant and Harrison, 2013 ; Thorpe and Harrison, 2008 ), black carbon ( Ali et al, 2020 ; Invernizzi et al, 2011 ), CO 2 ( Zheng et al, 2020 ) and nitrogen dioxide (NO 2 ) ( Agudelo-Castañeda et al, 2020 ; Degrauewe et al, 2019 ). In the literature there are many works on the quantification and modelling of the dispersion of pollutants from their sources.…”
Section: Introductionmentioning
confidence: 99%
“…Motor vehicle emissions are one of the primary sources of atmospheric particulate pollution in urban areas [ 10 , 35 , 36 ]. The particulate concentration distribution in the urban road environment generally exceeds that in the adjacent urban environment.…”
Section: Discussionmentioning
confidence: 99%
“…Another potentially relevant information was whether a study reported sea salt contribution to PM2.5. To better capture variability in the data, cities were assigned to 12 different regions mostly according to geographic proximity, and studies conducted by Karagulian et al (2015) and Heydari et al (2020). These are North America, Central Europe, East Asia, East/West Africa, Middle East, North-western Europe, Oceania/Japan, South/Central America, South-eastern Asia, Southern Asia, Southwestern Europe, and Western Europe.…”
Section: Review Framework and Study Selectionmentioning
confidence: 99%
“…Since the dose-response functions are non-linear, with a curve that is steep at low concentrations and flattens towards higher concentrations, there are diminishing returns of reduction in pollution levels at higher concentrations (Apte et al, 2018). The two factors (proportion of traffic and overall PM2.5 concentrations) vary greatly across the world (Heydari et al, 2020;Karagulian et al, 2015;WHO, 2018). For example, Heydari et al (2020) showed that traffic contribution estimates as well as uncertainties around these estimates vary largely across various cities and regions worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation